2020
DOI: 10.3390/cryst10020074
|View full text |Cite
|
Sign up to set email alerts
|

Improvement on Thermal Stability of Nano-Domains in Lithium Niobate Thin Films

Abstract: We present a simple and effective way to improve the thermal stability of nano-domains written with an atomic force microscope (AFM)-tip voltage in a lithium niobate film on insulator (LNOI). We show that nano-domains in LNOI (whether in the form of stripe domains or dot domains) degraded, or even disappeared, after a post-poling thermal annealing treatment at a temperature on the order of ∼100 ∘ C. We experimentally confirmed that the thermal stability of nano-domains in LNOI is greatly improved if a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…In paper [8] it was confirmed that the nano-domains in lithium niobate thin films are thermally unstable even at a temperature of the order of~100 • C, which can be easily reached due to light absorption. The thermal instability of nano-domains could be very detrimental to practical applications, such as periodically poled lithium niobate (PPLN) microcavities, PPLN ridge waveguides, and ferroelectric domain memories.…”
Section: Applications Of Lithium Niobate Waveguidesmentioning
confidence: 93%
“…In paper [8] it was confirmed that the nano-domains in lithium niobate thin films are thermally unstable even at a temperature of the order of~100 • C, which can be easily reached due to light absorption. The thermal instability of nano-domains could be very detrimental to practical applications, such as periodically poled lithium niobate (PPLN) microcavities, PPLN ridge waveguides, and ferroelectric domain memories.…”
Section: Applications Of Lithium Niobate Waveguidesmentioning
confidence: 93%
“…Nowadays, SPM is successfully used in LNOI wafers to create domain structures and domain imaging using piezoelectric force microscopy (PFM) [32][33][34][35][36][37]. Investigations have primarily been performed on Z-cut LNOI.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The thermal stability of the created domains after the preheat treatment has been shown recently. 20 The domain imaging at the cross section of LNOI by scanning transmission electron microscopy revealed the much stronger domain wall inclination, 21 compared to bulk LN crystals. 22,23 The further decrease in PPLN periods and increase in the domain pattern stability need the deeper study of the domain growth during local switching in LNOI wafers.…”
mentioning
confidence: 98%
“…15 The domain growth and interaction during local switching of LNOI wafers have been studied by piezoresponse force microscopy (PFM). [15][16][17][18][19][20] Formation of the stable isolated domains with charged domain walls (CDWs) and the absence of domain interaction have been found in LNOI wafers with a metal electrode under the LN film. [15][16][17] The thermal stability of the created domains after the preheat treatment has been shown recently.…”
mentioning
confidence: 99%